Earthquake Swarm Detection Along the Hikurangi Trench, New Zealand: Insights Into the Relationship Between Seismicity and Slow Slip Events. Issue 4 (6th April 2021) - Nishikawa, Tomoaki; Nishimura, Takuya; Okada, Yutaro
Abstract: Earthquake swarms, which are anomalous increases in the seismicity rate without a distinguishable mainshock, often accompany transient aseismic processes, such as fluid migration and episodic aseismic slip along faults. Investigations of earthquake swarm activity can provide insights into the causal relationship between aseismic processes and seismicity. Slow slip events (SSEs) along the plate interface in the Hikurangi Trench, New Zealand, are often accompanied by intensive earthquake swarms. However, the detailed spatiotemporal distribution of these earthquake swarms is still unclear. Here, we use the epidemic‐type aftershock‐sequence (ETAS) model to detect earthquake swarms ( M  ≥ 3) and create a new earthquake swarm catalog (1997–2015) along the Hikurangi Trench. We compare the earthquake swarm catalog with Global Navigation Satellite System (GNSS) time series data, and existing SSE and tectonic tremor catalogs. Most of the detected (119) earthquake swarm sequences were intraplate events, and their epicenters were mainly concentrated along the east coast of the North Island, whereas many tectonic tremors were located inland. Twenty‐five of the detected earthquake swarms occurred within 25 days before and after transient eastward GNSS displacements due to known or newly detected SSEs. We find that the earthquake swarms sometimes preceded the GNSS displacements by more than several days. SSE‐induced stress loading is therefore not a plausible triggering mechanism for these pre‐SSE earthquake swarms. We propose that high fluid pressure within the slab, which accumulated before the SSEs, may have caused intraplate fluid migration, which in turn triggered the pre‐SSE earthquake swarms. Key Points: We detected earthquake swarms in the Hikurangi Trench, New Zealand, and compared them with slow slip events (SSEs) and tectonic tremors Twelve of 49 earthquake swarms associated with transient eastward GNSS displacements caused by SSEs preceded the displacements by 5–25 days These pre‐SSE earthquake swarms might be triggered by intraplate fluid migration before the SSEs and not by SSE‐induced stress loading